Repeated in situ arterial thrombolysis in severe heparin-induced thrombocytopenia - Roxane Varone; Daniel Danzer (Annals of Vascular Surgery - Brief Reports and Innovations, 2023)
Unstructured abstract: There are no clear guidelines addressing the use of thrombolysis to treat acute limb ischemia in patients with heparin-induced thrombocytopenia. We report the case of a 75-year-old man presenting three episodes of acute limb ischemia, associated with type II heparin-induced thrombocytopenia, repeatedly treated by catheter-directed thrombolysis. Despite a thrombocyte count as low as 29 G/L, there were no bleeding complications. Catheter-directed thrombolysis seems safe to treat acute limb ischemia even with severe type II heparin-induced thrombocytopenia.